A Literature Survey on The Emerging Trends in The Telecommunications - Tilak Mukherjee (AG Volumes, 2022)
Improving telecommunications security and decreasing customer churn are two of the most pressing issues facing the telecom industry today, as well as optimising network load as well as infrastructure. These problems are dealt with head-on by the top ten trends in the telecommunications industry, which also serve to improve the overall efficacy of enterprises involved in the telecommunications industry. The global link that has been fostered by the COVID-19 outbreak provides telecommunications companies with a number of alternatives to build new products and grow their consumer base. In order to manage the growing number of people and things that are connected in smart industries, cities, homes, and automobiles, there is a growing need for cloud and 5G technology solutions. These solutions are needed to handle the flow of data generated by these connected environments.